Socioeconomic determinants of accessibility to birth registration in Lao PDR - Marika Nomura; Phonepadith Xangsayarath; Kenzo Takahashi; Yusuke Kamiya; Latsamy Siengsounthone; Hina Ogino; Jun Kobayashi (BMC, 2018)
Abstract Background The global coverage rate of birth registration is only around 65% for the population of children under five although birth registration secures protection and access to health services that are fundamental rights for all babies. This study aimed to perform a basic analysis of the accessibility to birth registration to better understand how to improve the birth registration system in the Lao PDR. Methods For the analysis of birth registration and related socioeconomic factors, 9576 mother-child pairs were chosen from the data set of The Lao Social Indicator Survey 2011-12. After bivariate analysis with statistical tests including the chi-square test were conducted, logistic regression was performed to determine the variables that statistically influence accessibility to birth registration. Results Ethno-geographic factors and place of delivery were observed to be the factors associated with birth registration in this analysis. Conclusion Many mothers in the Lao PDR deliver in their local communities. Therefore, capacity development of various human resources, such as Skilled Birth Attendant, to support the local administrative procedure of birth registration in their communities could be one option to overcoming the bottlenecks in the birth registration process in the Lao PDR.